Analisis Perkuatan Timbunan Di Atas Tanah Lunak Menggunakan Dinding Turap dengan Pendekatan Model Numerik - Hamdhan, Indra Noer; Iskandar, Fauziah Fitriani (MEDIA KOMUNIKASI TEKNIK SIPIL, 2019)
Embankment on soft clay may be affect settlement at subgrade, causing lateral deformation and vertical deformation around embankment. Therefore, reinforcement is needed to overcome the effects caused of the embankment. This research was conducted to find out the influence of sheet pile wall of embankment using PLAXIS 2D program based the finite element method. The analysis was done by varying of two condition, they are installation of sheet pile wall under the embankment and the sheet pile wall outside embankment. Sheet pile wall installation is carried out before embankment construction and length of sheet pile wall in this model is 15 m. The soil layers beneath the embankment consist of 10 m layer of soft clay layer and 5 m of sand layer. The height of embankment in this analysis is 8 m, where the constructing of the embankment was done in stages. The distance of sheet pile wall position under embankment from toe of embankment are -9 m, -6 m, -3 m, 0 m, 3 m dan 6 m. The results of analysis show the effective position for displacement are toe of embankment. The Installation of sheet pile walls below the embankment will reducing deformation up to 78% and the safety factor will increase up to 10%.